Internal and External Factors Affecting the Sales of Hype Drinks in Online Platform - Febrian, Fauzan; Ahmad, Nazmi Fathnur (Jurnal Minds: Manajemen Ide dan Inspirasi, 2021)
The Covid-19 Pandemic has hurt the beverage outlets' sales. This study investigates the strength of the internal and external factors that influenced sales in the online platforms of hype drinks. Thus, the study focused on the adaptation strategy to improve the sales in the online platform of hype drinks under environmentally-health pressures. The approach was mixed-method by obtaining the data through questionnaires, interviews, and observation. The participant in this study was consumer, employee, and owner. Data analysis is conducted under the SWOT analysis that has four steps in presenting the data. The finding concluded that internal and external factors positively impacted the business strategy to increase online sales of beverage outlets by riding the wave of hype among customers.